Assessment of pharmacists' knowledge, attitude and practice in chain community pharmacies towards their current function and performance in Indonesia - Athiyah U; Setiawan CD; Nugraheni G; Zairina E; Utami W; Hermansyah A (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: The introduction of universal healthcare coverage in 2014 has affected the practice of community pharmacies in Indonesia. Studies regarding the practice of pharmacist in the chain community pharmacy setting in Indonesia are very limited. The chain community pharmacies in Indonesia are operated and controlled by the same management. The chain community pharmacies usually show better services compared to independent community pharmacies in Indonesia. Objective: The study aimed to assess the knowledge, attitude and practice (KAP) of pharmacist working in chain community pharmacy towards their current function and performance in delivering pharmacy services Methods: A cross-sectional study using questionnaires was conducted between January and March 2017 in KF, one of the largest chain community pharmacies in Indonesia. The total sampling method was used in the recruitment process. The data were analyzed using descriptive statistics, independent t-Test and one-way ANOVA. The KAP scores were assessed and categorized as "poor", "moderate" and "good" based on the standardized scoring system. Results: A total of 949 KF's pharmacists (100% response rate) were participated in the study. The majority of pharmacists showed a good score in terms of knowledge and attitude, which is in contrast to practice as majority only obtained a moderate score. Working experience, age and the availability of standard operating procedures (SOP) for both dispensing and self-medication services were found to be statistically significant (p<0.005) aspects to KAP of pharmacists in delivering pharmacy services. Conclusions: This study identified several important aspects that could affect the KAP of pharmacists working in chain community pharmacies in Indonesia. Specific policies should be conceived to improve the competencies of pharmacist and to ensure the compliance with the SOP and standardization system within pharmacy sector.